Threading dislocations in La0.67Sr0.33MnO3/SrTiO3 superlattice. (1st September 2013) - He, Ming; Lin, Long; Tao, Hualong; Qiu, Minghui; Zou, Binyan; Zhang, Zhihua
Abstract : Transmission electron microscopy‐related experiments were performed on a La0.67 Sr0.33 MnO3 /SrTiO3 superlattice. The predominant defects in the superlattice are a high density of threading dislocations (TDs) perpendicular or quasi‐perpendicular to the substrate surface. The TDs are mostly pure‐edge‐type with Burgers vectors b = 〈100〉 or 〈110〉. A few TDs of screw character with Burgers vectors ± [001] were also found. Electron energy loss spectra show that non‐stoichiometry is accommodated in the near‐interface region of the superlattice. The stronger crystal field induced by defect and non‐stoichiometry are accounted for by the observed macroscopic properties.